Conventional periphrases of anthroponyms from a contrastive perspective (on the example of Polish periphrastic expressions and their Croatian equivalents) - Szerszunowicz, Joanna; Vidović Bolt, Ivana (Poznańskie Studia Slawistyczne, 2018)
The focal issue of the present paper is the conventional periphrasis as an object of contrastive research. Such expressions may have different cross-linguistic equivalents, including full, partial, parallel and zero counterparts. The present paper aims to discuss Polish periphrastic expressions and their Croatian equivalents in order to determine and analyze the relations between the units in question. The Polish units (165) are lexicographically attested, while their Croatian counterparts have been determined on the basis of dictionaries, corpora and interviews with native speakers of the Croatian language. The conventional periphrasis have not been researched from this perspective and the results may be useful for Polish-Croatian lexicography. The study shows that zero equivalents constitute the biggest group (91), followed by full equivalents (61) with significantly less numerous groups of partial and parallel counterparts (respectively: 5 and 8).